The Newly Unemployed and the UIF Take-up Rate : Implications for the Wage Subsidy Proposal in South Africa - Bhorat, Haroon (World Bank, Washington, DC, 2017)
This paper investigates the take-up rate or claim-waiting period rate of the unemployed under the South African Unemployment Insurance Fund (UIF) system. The goal is to identify disincentive effects that income replacement rates (IRR) and accumulated credits may have on the claimant's behavior in terms of their claim waiting period rate (or how quickly they apply for UIF benefits). Utilizing nonparametric and semi-parametric estimation techniques, we find that there is little evidence, if any, for job disincentives or moral hazard problems. More specifically, the majority of claimants that are quickest to claim the UIF benefits are those who have worked continuously for at least four years and accumulated the maximum allowable amount of credits. The authors also note that claimants' waiting periods are indifferent with regard to levels of income replacements yet extremely sensitive to the amount of credits accumulated. Ultimately, the recipients of the UIF benefits do not rely heavily on the replacement incomes and prefer waiting longer for employment opportunities as opposed to exhausting their accumulated credits. The semi-parametric Cox's Proportional Hazard (PH) model confirms that there is a positive relationship between the claimant's accumulation of credits and the associated take-up rate of the UIF.